Plant polysaccharides for protein binding - Gaanty Pragas, Maniam; Natanamurugaraj, Govindan; Palanisamy, Karthick Murugan; Kuppusamy, Palaniselvam; Mohd Hasbi, Ab. Rahim (Elsevier, 2023)
Polysaccharides are polymeric carbohydrates that are made up of many monosaccharide units linked together by glycosidic linkages. They are architecturally complex biomacromolecules because of the different monosaccharides and their infinite ways to form the building blocks with each other.